Empirical studies on informal patient payments for health care services: a systematic and critical review of research methods and instruments - Pavlova Milena; Stepurko Tetiana; Gryga Irena; Groot Wim (BMC, 2010)
Abstract Background Empirical evidence demonstrates that informal patient payments are an important feature of many health care systems. However, the study of these payments is a challenging task because of their potentially illegal and sensitive nature. The aim of this paper is to provide a systematic review and analysis of key methodological difficulties in measuring informal patient payments. Methods The systematic review was based on the following eligibility criteria: English language publications that reported on empirical studies measuring informal patient payments. There were no limitations with regard to the year of publication. The content of the publications was analysed qualitatively and the results were organised in the form of tables. Data sources were Econlit, Econpapers, Medline, PubMed, ScienceDirect, SocINDEX. Results Informal payments for health care services are most often investigated in studies involving patients or the general public, but providers and officials are also sample units in some studies. The majority of the studies apply a single mode of data collection that involves either face-to-face interviews or group discussions. One of the main methodological difficulties reported in the publication concerns the inability of some respondents to distinguish between official and unofficial payments. Another complication is associated with the refusal of some respondents to answer questions on informal patient payments. We do not exclude the possibility that we have missed studies that reported in non-English language journals as well as very recent studies that are not yet published. Conclusions Given the recent evidence from research on survey methods, a self-administrated questionnaire during a face-to-face interview could be a suitable mode of collecting sensitive data, such as data on informal patient payments.